Effects of moisture content on the behaviour of Scots pine heartwood and sapwood under impact - Hassan Vand, Mojtaba; Tippner, Jan (Springer Japan KK, 2024)
The material properties of sapwood and heartwood vary within various wood species and even they can show significant differences within a single tree. Scots pine (Pinus sylvestris L.), a species that plays a crucial role in timber production for joinery and building construction applications, is among those that show a notable distinction between its heartwood and sapwood. To examine the influence of moisture content (MC) on the impact behaviour of the sapwood and heartwood of pine, we tested specimens with two distinct moisture levels: a low moisture content (LMC) group with 12% MC and a high moisture content (HMC) group with 45% MC. In our study, we investigated deflection, normal strain and force development of the specimens during the short period of an impact, and also calculated the impact bending strength (IBS) of samples, using an impact testing machine equipped with a high-speed camera and digital image correlation method. Our results indicate that the differences between sapwood and heartwood at LMC were insignificant in the case of maximum deflection and normal strain, thus there is no need for differentiation; however, these differences became more pronounced, and non-negligible, with an increase in MC. We also evaluated the IBS of both heartwood and sapwood and found that, at LMC, heartwood had greater impact bending strength than sapwood, making it a preferable choice as a material subjected to impact loadings. Conversely, at HMC, both heartwood and sapwood would be equally strong against impacts, indicating that pine green wood shows no sensitivity to the ratio of sapwood to heartwood in the tree.
Keywords: Scots pine; Heartwood; Sapwood; Impact; Strain rate; Moisture content; Digital image correlation; Duration of load; Impact bending strength